Assessment dynamics at play in a collaborative research project with middle-school teachers in France - Younès, Nathalie; Faidit, Claire (Mesure et évaluation en éducation, 2020)
This study deals with the dynamics of assessment at play in collaborative research carried out with two multidisciplinary teams of French middle-school teachers. It shows how connecting the teachers’ experience with the outside frame of reference, through a reflexive, critical, but also prospective approach of assessment for learning (AfL) methodology, produces both referentialization and subjectification/intersubjectification, enabling individual and collective professional development. Collective creation of a common frame of reference through students’ development and usage of criteria assessment grids brings about varied implementations and understandings among teachers when the assessment is actually conducted. Experimenting with this hybrid construct in the classroom and discussing it by confronting the activity’s actual outcome with its projected result open new insights and perspectives that lead to a broader referentialization of AfL and renewed professional identity.